2011
DOI: 10.1007/s12046-011-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the microstructures and properties of metal inert gas and friction stir welds in aluminum alloy 5083

Abstract: Two different types of welds, Metal Inert Gas (MIG) and Friction Stir Welding (FSW), have been used to weld aluminum alloy 5083. The microstructure of the welds, including the nugget zone and heat affected zone, has been compared in these two methods using optical microscopy. The mechanical properties of the weld have been also investigated using the hardness and tensile tests. The results show that both the methods could successfully be used to weld such alloy. The strength of the joints is comparable to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Moreover, FSW may offer a choice of resultant microstructure characterized by a refined mixture of ferrite and cementite, pearlite, bainite, or martensite, by simply altering the welding parameters. The comparison between MIG and FSW of aluminum alloy Al 5083, reported by Yazdipour et al [18], indicated the distinct grain morphology in the welded zones. While the weld zone of the MIG specimen was characterized by larger grains than the parent metals, the FSW specimen was characterized by very fine equiaxed grain morphology.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, FSW may offer a choice of resultant microstructure characterized by a refined mixture of ferrite and cementite, pearlite, bainite, or martensite, by simply altering the welding parameters. The comparison between MIG and FSW of aluminum alloy Al 5083, reported by Yazdipour et al [18], indicated the distinct grain morphology in the welded zones. While the weld zone of the MIG specimen was characterized by larger grains than the parent metals, the FSW specimen was characterized by very fine equiaxed grain morphology.…”
Section: Introductionmentioning
confidence: 90%
“…The weld nugget or the stirred zone consists of fineequiaxed recrystallized grains that are formed due to high temperature and high deformation rate in the weld nugget due to the stirring caused by the tool pin [26]. Bent elongated grains can be observed near the nugget which is the TMAZ [27]. The zone next to the TMAZ is the HAZ, this zone will experience thermal cycle, but will not undergo any plastic deformation.…”
Section: Effect Of Microstructure On Tensile Propertiesmentioning
confidence: 99%
“…Se conoce además que la soldabilidad en uniones soldadas está determinada entre otros por los siguientes factores: i) Compatibilidad química y fluidez del material base y de aporte; ii) Temperatura de fusión, calor especifico, alta conductividad y nivel de expansión térmica; iii) Estabilidad del arco, naturaleza refractaria del óxido de aluminio, características de color similares cerca del punto de fusión y atmosfera de protección; iv) Requerimientos de precalentamientos y tratamientos térmicos antes, durante y post soldadura; v) Tensión superficial característica del depósito de soldadura fundido; vi) Consideraciones de esfuerzos residuales, rigidez, ductilidad, fatiga y resistencia a la corrosión tanto del material base, material de aporte y depósito de soldadura; y vii) Consideraciones de diseño y desarrollo para la fabricación y ensamble de productos soldados. Un control efectivo del calor aportado se logra, además, utilizando procesos adecuados de soldadura, con gas de protección GMAW, GTAW y por fricción-agitación (Yazdipour et al, 2011) y otras técnicas de soldadura que garanticen una ZAT mínima.…”
Section: Soldabilidadunclassified